2019
DOI: 10.5539/jas.v11n6p556
|View full text |Cite
|
Sign up to set email alerts
|

Urochloa Hybrid Submitted to Biostimulant Application in Grazing Simulation

Abstract: The objective of this work was to evaluate the performance of Urochloa hybrid Convert HD364 applied in different doses as a vegetable biostimulant under grazing simulation in intermittent stocking in the city of Uberlândia, Minas Gerais. The treatments consisted of a control (absence of biostimulant) and in 5 doses of biostimulant, 0.25; 0.5; 0.75; 1.0 and 1.25 L ha-1, in a randomized complete block design with 4 replicates. Productive and qualitative parameters were evaluated. The data were submitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The decrease in the L:S ratio may be related to the increasing biostimulant doses, which provided a higher dry matter accumulation in the stems compared to the leaves and, consequently, a decrease was found in this relationship. Lima et al (2019) reported a 5.91% reduction in the L:S ratio when applying 0.75 L ha −1 of biostimulant on forage of the genus Urochloa.…”
Section: Table 3 Chemical Characteristics Of Marandu Grass Submitted mentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the L:S ratio may be related to the increasing biostimulant doses, which provided a higher dry matter accumulation in the stems compared to the leaves and, consequently, a decrease was found in this relationship. Lima et al (2019) reported a 5.91% reduction in the L:S ratio when applying 0.75 L ha −1 of biostimulant on forage of the genus Urochloa.…”
Section: Table 3 Chemical Characteristics Of Marandu Grass Submitted mentioning
confidence: 99%
“…In this sense, biostimulants have been used mainly in systems that aim for precision agriculture (Oliveira et al, 2019;Lima et al, 2019). Biostimulants are complexes that contain substances such as auxins, gibberellins, cytokinins, and their analogs, which act mainly in the regulation of growth, elongation, and cell division (Santos et al, 2017), favoring the expression of the genetic potential of the plant and, consequently, stimulating the shoot and root system growth (Magalhães et al, 2016).…”
Section: Introductionmentioning
confidence: 99%